1986
DOI: 10.1111/j.1600-0722.1986.tb01380.x
|View full text |Cite
|
Sign up to set email alerts
|

Monkey pulp reactions to restorative materials

Abstract: — Deep buccal cavities in 99 teeth in eight young monkeys were filled with the following combination of materials: a light‐cured microfilled composite with or without a base, a chemically cured composite with a base, a silicate cement, and a zinc oxide‐eugenol cement. The acid etch technique and intermediate layer of resin was used in the composite group. Pulp reactions and presence and location of bacteria were studied after 8 days and after 90 days. In the short observation period the inflammatory reactions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1987
1987
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…The most pronounced inflammatory reactions were seen when bacteria were found in the dentinal tubules, in agreement with previous findings (16). Unacceptable inflammatory reactions were especially seen in Group One where neither Procal nor Gluma Dentin Bond was used.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The most pronounced inflammatory reactions were seen when bacteria were found in the dentinal tubules, in agreement with previous findings (16). Unacceptable inflammatory reactions were especially seen in Group One where neither Procal nor Gluma Dentin Bond was used.…”
Section: Discussionsupporting
confidence: 91%
“…Prior to the operative procedures the teeth were polished with pumice and rinsed with airwater spray. Deep buccal class V cavities were cut in 72 incisors and canines using an inverted earbide bur in an airturbine with water spray (16). Tbe cavities were beveled with a small round diamond bur in a conventional speed bandpiece.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In humans, pulp exposures in cavities cleaned with Tubulicid® and restored with unlined composite resin overlayed with zinc oxide-eugenol remained vital and showed no signs of inflammation (42). Of the commonly used restorative materials, zinc oxide-eugenol cements have been consistently proven to prevent bacterial microleakage (43,44). An in vitro study indicates that glass ionomer cements exhibit antibacterial properties (45), although an animal study found that different proprietary products exhibited great variation in their ability to prevent bacterial penetration, with only one commercial product approaching the effectiveness of zinc oxide-eugenol (46).…”
Section: Bactariai Contaminationmentioning
confidence: 99%